2020
DOI: 10.1088/1742-6596/1691/1/012161
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of using G Suite for Education services in the educational process of Polotsk State University

Abstract: The article begins by defining e-learning as the use of technology for teaching and learning. There is a significant interest in identifying the advantages, disadvantages and challenges of using information technologies in the studying process for full-time studying, where e-learning is a component of the educational process, rather than a substitute for it. The article then turns to a practical case study of e-learning in Polotsk State University. The indicators and features of use of the G Suite for Educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Literature related to student perceptions focuses on students' feelings and perceptions about the use of social media for learning. Studies reported that students feel positively about the impact of social media on the learning environment, their cognitive skills and their interactions (Barun et al, 2020;Daniels and Billingsley, 2014;Fosu et al, 2019;Mondahl and Razmerita, 2014). For example, in Daniels and Billingsley's (2014) study, students perceived the class Facebook group as a helpful tool for communication and collaboration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Literature related to student perceptions focuses on students' feelings and perceptions about the use of social media for learning. Studies reported that students feel positively about the impact of social media on the learning environment, their cognitive skills and their interactions (Barun et al, 2020;Daniels and Billingsley, 2014;Fosu et al, 2019;Mondahl and Razmerita, 2014). For example, in Daniels and Billingsley's (2014) study, students perceived the class Facebook group as a helpful tool for communication and collaboration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in Daniels and Billingsley's (2014) study, students perceived the class Facebook group as a helpful tool for communication and collaboration. More recently in a study by Barun et al (2020), students perceived the use of Google Suite as positive and as a useful tool for learning. In another study, students positively believed that the use of Twitter, in combination with the LMS, could be beneficial for learning and hoped for more integration of social media for teaching (Fosu et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of attention is drawn to the use of Google Classroom and Google Meet. In particular, researchers analyze the functional advantages of Google Classroom for learning [14], they study the factors affecting students' perception of the Google Classroom platform (hedonic motivation, social influence, habit [15], usefulness, simplicity of use [16], [17], etc.). If we take into account Google Meet, researchers study the level of students' awareness about the possibilities of this tool in the conditions of distance learning [18], the level of satisfaction from its use in the educational process [19].…”
Section: Introductionmentioning
confidence: 99%